Type D personality to insomnia: Sleep reactivity, sleep effort, and sleep hygiene as mediators - Uygur, Omer Faruk; Ahmed, Oli; Uygur, Hilal; Bahar, Aynur; Hursitoglu, Onur; Chung, Seockhoon; Drake, Christopher L. (Frontiers in Psychiatry, 2023)
Background: Insomniacs are heterogenous group with very diverse personalities. We aimed to investigate the mediating role of sleep reactivity (SR), sleep hygiene (SH), and sleep effort (SE) in the relationship between Type D personality and insomnia. Materials and Methods: We conducted a cross-sectional survey among 474 participants. The survey comprised the sociodemographic data form, Insomnia Severity Index (ISI), D Type Personality Scale (DS-14), Ford Insomnia Response to Stress Test (FIRST), Glasgow Sleep Effort Scale (GSES), and Sleep Hygiene Index (SHI). We conducted hierarchical multiple regression analysis to identify the associations between age, sex, SR, Type D personality traits, SE, SH, and insomnia severity. We subsequently conducted mediation analyses to examine whether SR, SH, and SE mediated the relationship between Type D personality and insomnia. Results: ISI, DS-14, FIRST, SHI, and GSES scores were significantly higher in individuals with Type D personality. Female sex, SR, Type D personality traits, SE, and SH explained 45% of the variance in insomnia severity. When age, sex, insomnia response to stress, and Type D personality traits were controlled, SE and SH significantly explained 25% of the variance in insomnia severity (R2= 0.45, R2 change= 0.25, F (6.474) = 65.58, p < 0.001). SR, SE, and SH each played a partial mediating role between Type D personality and insomnia. Conclusions: The findings showed that individuals with Type D personality had high SR and that individuals with a higher number of these personality traits exhibited more severe insomnia symptoms through high SR, greater SE, and worse SH.